1999
DOI: 10.1111/j.1349-7006.1999.tb00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent p53 Gene Mutations in Soft Tissue Sarcomas Arising in Burn Scar

Abstract: Squamous cell carcinoma (SCC) is the commonest malignancy that arises in burn scars, which frequently contain p53 mutations. Soft tissue sarcoma (STS) also develops, though less frequently, in burn scars. p53 gene mutations were analyzed in paraffin-embedded specimens from 5 patients with STS (4 males and 1 female) that had arisen in a burn scar, by means of polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) followed by direct sequencing. Age at burn injury ranged from 2 to 10 (median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…There is a strong correlation between p53 inactivation and the development of soft tissue sarcoma. 5,9) However, although p53 inactivation and development of glioma are related, other biological molecular events, e.g. PTEN mutation, p16 inactivation, and epidermal growth factor receptor amplification, are also involved.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong correlation between p53 inactivation and the development of soft tissue sarcoma. 5,9) However, although p53 inactivation and development of glioma are related, other biological molecular events, e.g. PTEN mutation, p16 inactivation, and epidermal growth factor receptor amplification, are also involved.…”
Section: Discussionmentioning
confidence: 99%
“…These include the development of DFSP at sites of trauma ranging from 'vaccination to bayonet wound' [2], such as surgical scars [25][26][27], burn scars [28,29], sites of prior immunisation [4][5][6][7] and therapeutic irradiation [12,30]. In addition, increased frequency of trauma to the hands and feet is thought to account for the higher incidence of acrally occurring DFSP in children and adolescents compared to adults [12].…”
Section: Aetiologymentioning
confidence: 99%
“…Those cases reported to date include the development of DFSP at sites of surgical scars, burn scars, and at sites of prior immunisation and therapeutic irradiation [2][3][4][5][6][7][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…10 A recent study reported mutations in p53 in 4 of 5 human soft tissue sarcomas arising in old burn scars. 9 The authors speculated that missense mutations arise in conserved regions of p53 because of the effects of oxygen radicals generated during inflammation. Burnscar carcinomas were fatal in 1 of 3 affected patients, according to 1 large retrospective study.…”
mentioning
confidence: 99%
“…More than 50 viruses have been isolated from Culicoides species, including the agents responsible for African horse sickness, bluetongue, epizootic hemorrhagic disease, and Akabane disease. 2,8,9 Female Culicoides incise the skin of mammalian and avian hosts using a sawing action by paired, toothed mandibular stylets. Unlike mosquitoes, which canulate the dermal microvasculature, biting midges are ''pool feeders'' that sever dermal vessels with cutting mouthparts to obtain a blood meal.…”
mentioning
confidence: 99%